INTRA-ABDOMINAL HYPERTENSION IN PATIENTS UNDERGOING OPEN ABDOMINAL SURGERY AT THE SURGICAL INTENSIVE CARE UNIT - THANH NHAN HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: Increased intra-abdominal pressure after abdominal surgery is a common complication in patients in the postoperative intensive care unit, especially in major surgeries such as gastrointestinal, hepatobiliary, or abdominal trauma surgeries. This study aimed to evaluate the prevalence of increased intra-abdominal pressure in patients after gastrointestinal surgery in the Surgical Intensive Care Unit, Thanh Nhan Hospital. Method: A descriptive cross-sectional study with longitudinal follow-up of response in abdominal surgery patients whose intra-abdominal pressure was monitored via bladder catheter in the Surgical Intensive Care Unit, Thanh Nhan Hospital from April 2021 to October 2021. Results: The study was conducted on 25 patients who underwent abdominal surgery and whose intra-abdominal pressure was monitored via bladder catheter. The proportion of males was nearly twice that of females, with an average age of 67.7 ± 13.9 years and an average BMI of 20 ± 3 kg/m2. The surgeries performed were primarily colon surgery (32%) and gastric surgery (28%), all of which were emergency surgeries. Postoperative complications occurred in 12% of cases. The rate of increased intra-abdominal pressure (IAP) was relatively high at 36%, mainly grade I (20%), with other grades less common (less than 10%). Patients with postoperative complications had a higher rate and severity of IAP, with 66.67% grade III and 33.33% grade IV. IAP typically appeared after 48 ± 9.8 hours and peaked between the 8th and 10th day. Conclusion: Increased intra-abdominal pressure is a common complication in patients undergoing abdominal surgery; however, the degree of increased intra-abdominal pressure was mainly grade I and appeared early, on day 1 post-surgery.
Keywords: Abdominal surgery, increased intra-abdominal pressure..